Heart disease and erythropoietin. (January 2008) - Rao, K Nayan S; Binbrek, Azan S; Sobel, Burton E
An additional target for reducing infarct size, namely, attenuation of apoptosis, has recently emerged. Erythropoietin (Epo) exhibits properties that may attenuate this process and enhance neovascularization, thereby preserving jeopardized myocardium. Potentially adverse effects of Epo, including hypertension, thrombosis and possible exacerbation of occult neoplasms can likely be averted with analogues such as carbamylated and asialo Epo, which are devoid of erythropoietic effects, yet retain tissue-protective characteristics. With a single, but adequate dose of Epo administered early after the onset of acute myocardial infarction, coupled with therapy to induce reperfusion, tissue protection conferred by Epo and its analogues may facilitate the preservation of myocardium subjected to ischemic insults, thereby improving prognosis.